The Effectiveness of Solution-oriented Group Teaching on the Increase of Resiliency in Orphan Female Adolescents - Maryam Adibi; Yousef Gorgi (Journal of Social Behavior and Community Health)
Background: The absence of one of the parents can bring about major problems in adolescents’ psychological conditions. The objective of the present study was therefore to investigate the effectiveness of solution-oriented group consultation on the increase of resiliency in orphan (fatherless) female adolescents in the city of Isfahan. Methods: The present study was quasi-experimental with pretest, post-test, follow-up and control group research design. The statistical population of the study included all orphan (fatherless) female students in the city of Isfahan in the academic year 2014-2015. Convenient sampling method was used to select the samples; hence, 40 female adolescents were selected as the sample size and were assigned into two groups of 20. eight ninety-minute therapeutic interventions (solution-oriented approach) was administered on the experimental group once a week. The control group, however, did not receive any teaching. Connor-Davidson Resilience Scale was used as the study instrument. And the collected data were analyzed through repeated measures ANOVA via SPSS23 software. Results: The results of the study showed the solution-oriented group teaching being effective on the resiliency of orphan adolescents at the post-stage and follow-up stages (p<0.001). Conclusion: Predicated on the findings of the present study, the solution-oriented teaching method can be applied to increase orphan (fatherless) female adolescents’ resiliency.